1300mpa grade acid medium corrosion resistant ultrahigh strength steel plate and production method thereof

CN118326249BActive Publication Date: 2026-10-16BAOSHAN IRON & STEEL CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202310035480.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-10
Publication Date
2026-10-16
Estimated Expiration
2043-01-10

AI Technical Summary

Technical Problem

但是没有考虑腐蚀性能,不满足酸性介质下的耐磨使用要求

Benefits of technology

[0073] In terms of composition design, this invention supplements the C-Mn base with small amounts of Nb, Ti microalloying elements, and Cu, Cr, Al, Mo, etc. Cu, Mo, and Cr enhance the steel's strength; the synergistic effect of Cu and Cr increases the matrix potential; and the combination of Al and Mo, satisfying the relationship Cr/(Mo/1.85+1.93Al)≥1.8, improves the self-corrosion potential and charge transfer resistance of the steel in acidic media containing large amounts of sulfate and chloride ions, reduces the corrosion current density, and thus enhances the steel's corrosion resistance. Furthermore, it was found that the aggregation of intermetallic compounds formed by Mo, Cr, and Al on the steel surface can further improve the steel's corrosion resistance. While ensuring high strength and high hardness, this invention also provides excellent corrosion resistance in acidic media. Moreover, the steel plate obtained by this invention exhibits good low-temperature impact toughness and cold bending performance, meeting the requirements of subsequent processing and use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118326249B_ABST
    Figure CN118326249B_ABST
Patent Text Reader

Abstract

The application discloses a 1300MPa-grade acid medium corrosion-resistant ultrahigh-strength steel plate and a production method thereof. The ultrahigh-strength steel plate has the following chemical components in percentage by weight: C 0.17-0.22%, Si 0.10-0.30%, Mn 0.80-1.20%, P≤0.018%, S≤0.010%, Al 0.015-0.15%, Cu 0.15-0.35%, Cr 0.50-1.20%, Mo 0.02-0.15%, B 0.0010-0.0030%, N≤0.005%, one or both of Nb 0.01-0.03 and Ti 0.01-0.03, and the balance including Fe and other inevitable impurities; and the following relationship is satisfied: Cr / (Mo / 1.85+1.93Al)≥1.8. The ultrahigh-strength steel plate has high strength, high hardness and excellent corrosion resistance in an acid corrosion medium, the yield strength of the ultrahigh-strength steel plate is≥1100MPa, the tensile strength is≥1300MPa, the elongation is≥12%, the hardness is 450±30HBW, the impact energy at-40 DEG C is≥60J, the corrosion resistance is more than 4 times of that of plain carbon steel, and the relative corrosion rate is less than 25%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of low alloy steel manufacturing, specifically to a 1300MPa grade acid-resistant ultra-high strength steel plate and its production method. Background Technology

[0002] Dump truck bodies experience wear and tear when transporting sand and gravel, especially mining dump trucks, where wear is particularly severe. Therefore, the strength of steel used in dump truck bodies has been gradually increased, from the previous 345MPa ordinary carbon steel to 700MPa, 960MPa, and even 1300MPa grades to improve wear resistance. In some special applications, such as grab buckets for loading and unloading corrosive minerals and sanitation truck bodies for transporting domestic waste, structural components not only experience wear but also significant corrosion. Under such acidic corrosive media, material failure is rapid, and even areas without wear develop noticeable pitting, severely shortening the equipment's service life.

[0003] Chinese patent CN103103448A discloses a "low-alloy high-strength and high-toughness wear-resistant steel plate," which, in its composition design, adds higher levels of Mo and Si to a C-Mn base. This steel achieves a hardness of 450 HBW and is mainly used in engineering machinery, mining equipment, and other fields, exhibiting good wear resistance. However, it does not consider corrosion resistance and does not meet the wear resistance requirements under acidic media.

[0004] Japanese Patent JP2007231321A discloses "wear resistant steel sheet" and Japanese Patent JP2008169443A discloses "wear-resistant steel sheet superior in workability and manufacturing method therefor", which introduce methods to improve wear resistance by precipitating Ti and W carbide particles. However, the hardness of the former is basically between 396-431 HBW, while that of the latter is less than 300 HBW, and the problem of acid corrosion resistance is not considered.

[0005] Japanese Patent JP2001164335A discloses "a steel plate with good weldability and machinability resistant to sulfuric acid dew point corrosion," which is suitable for equipment and power plants that burn heavy oil. Although this steel meets the requirements for acidic media corrosion, the steel plate has low strength and is not wear-resistant.

[0006] Chinese patent CN103397272A, entitled "Wear-resistant steel plate with low crack sensitivity index and high strength and its preparation method," involves steel grades with a hardness of up to 450 HBW, mainly used in engineering machinery, mining equipment, and other fields, exhibiting good wear resistance. However, it does not consider corrosion resistance and does not meet the wear resistance requirements under acidic media.

[0007] Chinese patent CN108930001A discloses "A high-hardness wear-resistant and corrosion-resistant steel plate for slurry dredging and its production method", which is an ultra-high-strength wear-resistant and corrosion-resistant steel plate with a strength of 450HBW. The composition design mainly takes into account the corrosion problem in the seawater environment. It is mainly used for the processing of dredging pipes and does not involve acidic media corrosion.

[0008] Chinese patent CN102268613A2011 discloses "A hot-rolled steel plate resistant to atmospheric corrosion for railway freight cars and its manufacturing method". Although acidic media corrosion is taken into account, it is essentially a hot-rolled steel plate with a yield strength of only 450MPa and no wear resistance.

[0009] In fields such as aluminum ore slurry and municipal solid waste treatment, materials contain acidic corrosion and a large number of sulfate and chloride ions. Equipment that comes into contact with slurry and powder, such as dump truck bodies, grab buckets, sanitation vehicle bodies, and chemical pipelines, faces not only wear and tear but also the problem of acidic media corrosion. These media are generally weakly acidic, and under conditions of wear and tear, corrosion and wear mutually promote each other, significantly increasing material failure and shortening equipment lifespan.

[0010] Currently, high-strength steels with wear resistance properties do not take into account corrosion resistance, or do not consider corrosion resistance in acidic media containing large amounts of sulfate and chloride ions; and the few steels that are resistant to acidic media corrosion are mainly hot-rolled steel plates with yield strength mostly at the 450MPa level, which is far from meeting the requirements for wear resistance. Summary of the Invention

[0011] The purpose of this invention is to provide a 1300MPa grade acid-resistant ultra-high strength steel plate and its production method. The ultra-high strength steel plate achieves high strength and hardness while exhibiting excellent corrosion resistance and wear resistance under acidic corrosive media. The ultra-high strength steel plate has a yield strength ≥1100MPa, tensile strength ≥1300MPa, elongation ≥12%, hardness 450±30HBW, impact energy at -40℃ ≥60J, and corrosion resistance more than four times that of ordinary carbon steel, with a relative corrosion rate of less than 25%. It can be used to manufacture mining equipment, dump truck bodies, sanitation vehicle bodies, chemical equipment, etc., effectively extending the service life of equipment and reducing costs.

[0012] To achieve the above objectives, the technical solution provided by this invention is as follows:

[0013] A 1300MPa grade acid-resistant ultra-high strength steel plate has the following chemical composition by weight percentage: C: 0.17–0.22%, Si: 0.10–0.30%, Mn: 0.80–1.20%, P≤0.018%, S≤0.010%, Al: 0.015–0.15%, Cu: 0.15–0.35%, Cr: 0.50–1.20%, Mo: 0.02–0.15%, B: 0.0010–0.0030%, N≤0.005%, containing one or both of Nb (0.01–0.03%) and Ti (0.01–0.03%), with the balance including Fe and other unavoidable impurities; and the above elements must simultaneously satisfy the following relationship:

[0014] Cr / (Mo / 1.85+1.93Al)≥1.8.

[0015] Furthermore, the balance consists of Fe and other unavoidable impurities.

[0016] Furthermore, the steel plate composition also includes one or more of the following: W: 0.01-0.5%, Sb: 0.02-0.12%, RE: 0.02-0.12%, V: 0.02-0.12%, and Ca: 0.001-0.010%.

[0017] The microstructure of the ultra-high strength steel plate described in this invention is martensitic.

[0018] The steel plate of the present invention has a yield strength ≥1100MPa, tensile strength ≥1300MPa, elongation ≥12%, hardness 450±30HBW, impact energy value at -40℃ ≥60J, corrosion resistance is more than 4 times that of ordinary carbon steel, and relative corrosion rate is less than 25%.

[0019] In the composition design of the steel plate described in this invention:

[0020] Carbon: the cheapest strengthening element in steel, which can significantly improve the strength of steel plates. However, too much carbon is detrimental to the welding, toughness and plasticity of steel plates. Therefore, this invention controls the carbon content to be 0.17-0.22%.

[0021] Silicon (Si): Si is a deoxidizing element, a solid solution strengthening element, and a commonly used corrosion-resistant element in atmospheric corrosion-resistant steels. In steel, Si replaces Fe atoms through substitution, hindering dislocation movement and thus achieving solid solution strengthening. Simultaneously, Si can reduce the diffusion coefficient of C in ferrite, increase carbon activity, inhibit carbide formation, and suppress the precipitation of coarse carbides at defects, thereby improving toughness. However, excessively high Si content can promote graphitization of C, which is detrimental to toughness, surface quality, and weldability. Therefore, this invention controls the Si content to be 0.10–0.30%.

[0022] Manganese: It is also a common strengthening element in steel. It can improve yield strength and reduce elongation through solid solution strengthening. At the same time, it can significantly reduce the phase transformation temperature of steel and refine the microstructure of steel. It is an important strengthening and toughening element. However, excessive Mn content increases hardenability, which leads to deterioration of weldability and toughness of the weld heat-affected zone and increases cost. Therefore, the present invention controls the Mn content to be 0.80 to 1.20%.

[0023] Phosphorus is a major corrosion-resistant element in traditional atmospheric corrosion-resistant steels, promoting the formation of a protective rust layer and effectively improving the steel's atmospheric corrosion resistance. However, during corrosion and wear, the formation of the rust layer accelerates material weight loss, reducing wear resistance. Furthermore, the presence of phosphorus easily leads to segregation, reducing the steel's toughness and plasticity, and making the steel plate brittle and affecting its toughness. Therefore, the phosphorus content in steel should be minimized. However, excessively low phosphorus control requirements simultaneously increase alloy costs and steelmaking difficulty. Therefore, this invention controls phosphorus content to ≤0.018%.

[0024] Sulfur: It can increase the yield strength of steel, but it easily forms manganese sulfide, a plastic inclusion, with Mn during solidification, which is detrimental to transverse plasticity and toughness. In the presence of V, fine MnS will promote the precipitation of fine VN, which serves as a nucleation site for intragranular ferrite (IGF), refining the ferrite-pearlite structure and improving strength and toughness. However, the presence of S will worsen the corrosion performance of steel, make the steel plate brittle, and reduce the low-temperature toughness of steel. Therefore, this invention controls S ≤ 0.010%.

[0025] Aluminum: Typically added to steel during the steelmaking process as a deoxidizer. Trace amounts of Al help refine grains and improve the strength and toughness of the steel. Adding appropriate amounts of Al increases the corrosion potential of the steel, which helps inhibit corrosion. Simultaneously, the addition of Al and Si can form complex nanoscale oxides within the steel plate. The formation and accumulation of these oxides in the inner rust layer can increase the charge-mass transfer resistance, thereby inhibiting the corrosion process. However, Al reduces austenite stability and austenite undercooling, causing rapid growth of new phase nuclei, thus reducing hardenability and increasing the critical quenching rate. Furthermore, as a ferrite-forming element, excessive Al can reduce the strength of the steel plate, increase the brittleness of ferrite, and lead to a decrease in steel toughness. Therefore, this invention controls the Al content to be 0.015–0.15%.

[0026] Boron: It has good hardenability, thereby improving the hardness of steel plates. However, excessive B content is detrimental to weldability. Therefore, the present invention controls the B content to be 0.001-0.003%.

[0027] Copper: It possesses solid solution and precipitation strengthening properties. At higher content, it exhibits a secondary hardening effect upon tempering at appropriate temperatures, thereby increasing the strength of the steel plate. Simultaneously, Cu also enhances the corrosion resistance of steel plates. Its electrochemical potential is higher than that of Fe. Adding an appropriate amount of Cu, on the one hand, helps increase the self-corrosion potential of the steel plate itself, reducing the corrosion rate; on the other hand, it promotes the densification and stabilization of the rust layer on the steel surface, thus improving corrosion resistance. Especially in acidic media, Cu combines with residual S in the steel to form a Cu₂S protective film, mitigating corrosion in acidic environments. Excessive Cu content can cause cracks in the steel billet during heating and hot rolling, deteriorating surface properties. Therefore, this invention controls the Cu content to be 0.15–0.35%.

[0028] Chromium: In steel, Cr forms a continuous solid solution with Fe, resulting in solid solution strengthening. It also forms various types of carbides with C, such as M3C, M7C3, and M... 23 C6, etc., produce a secondary strengthening effect. Cr shrinks the austenite region, reduces the diffusion rate of C in austenite, lowers the critical cooling rate, and improves the hardenability and tempering stability of the steel plate. Therefore, wear-resistant steels usually have a certain amount of Cr added to obtain high strength and hardenability. In this patent, the addition of Cr is mainly to improve corrosion resistance in acidic media. Cr has a significant effect on improving the passivation ability of steel, promoting the formation of a dense passivation film or protective rust layer on the steel surface, and forming FeCr2O4 with good anti-corrosion function in the rust layer. Its enrichment in the rust layer can effectively improve the selective permeability of the rust layer to corrosive media; at the same time, the addition of Cr can effectively increase the self-corrosion potential of steel, inhibit the occurrence of corrosion, thereby effectively reducing the promoting effect of corrosion on material failure during the abrasion process and improving wear resistance. In particular, the combination of Cr and Cu improves the corrosion resistance in acidic media. Wear-resistant steel contains a high amount of carbon (C), which forms a supersaturated solid solution after heat treatment. While this improves strength and hardness, it also deteriorates corrosion resistance. The addition of an appropriate amount of chromium (Cr) compensates for the reduced corrosion resistance caused by C; the Cr content should not be less than 0.5%. Excessive Cr content is detrimental to toughness and increases welding difficulty. Furthermore, Cr is a valuable alloying element; therefore, the Cr content is controlled at 0.5–1.2% in this invention.

[0029] Molybdenum (Mo) can exist in steel in solid solution, resulting in solid solution strengthening. During quenching heat treatment, Mo promotes the formation of martensite, exhibiting phase transformation strengthening and dislocation strengthening effects. Simultaneously, Mo increases the solubility of Nb, V, and Ti, promoting precipitation strengthening. The addition of Mo improves the corrosion product film structure, enhancing the steel's resistance to pitting corrosion, crevice corrosion, and other localized corrosion. In this invention, the combination of Cr, Al, and Mo significantly improves corrosion resistance in acidic media. However, higher Mo content is detrimental to weldability and increases cost. Therefore, this invention controls the Mo content to be 0.02–0.15%. To further ensure corrosion resistance in acidic media, the content of Cr, Al, and Mo is limited to satisfy the relationship: Cr / (Mo / 1.85+1.93Al)≥1.8.

[0030] Niobium (Nb) is a strong nitrogen carbide-forming element, capable of combining with carbon and nitrogen in steel to form intermediate phases such as NbC, Nb(CN), and NbN. The resulting fine carbide particles refine the microstructure, producing precipitation strengthening and significantly improving the strength of the steel plate. Furthermore, Nb inhibits the expansion of austenite interfaces, raising the recrystallization temperature of the steel and enabling rolling in the non-recrystallization zone at higher temperatures. Therefore, adding an appropriate amount of Nb to steel is beneficial for strength improvement. The carbonitrides formed by Nb can pin austenite grain boundaries during austenitization, inhibiting abnormal austenite grain growth and improving the toughness of the steel plate after quenching. However, excessive Nb is detrimental to welding, and it readily forms brittle metallic hydrides with hydrogen. These hydrides exhibit significant differences in ductility and toughness compared to the matrix, and their bonding strength with the matrix is ​​also poor, leading to delayed cracking. Therefore, in this invention, the Nb content is controlled at 0.01–0.03%.

[0031] Titanium plays a crucial role in two aspects: firstly, it inhibits austenite grain growth during slab reheating; secondly, it suppresses ferrite grain growth during recrystallization controlled rolling, thereby improving the steel's toughness. Furthermore, Ti preferentially combines with nitrogen (N) in the steel, reducing the amount of AlN. However, excessively high Ti content is detrimental to low-temperature impact toughness. Therefore, in this invention, the Ti content is controlled at 0.01–0.03%.

[0032] Nitrogen: In steel, nitrogen (N) can form fine nitrides with Nb, V, and Ti. These fine nitride precipitations act as grain boundary pinning agents, refining austenite grains. The precipitated nitrides also have a precipitation strengthening effect. However, higher levels of N in steel readily combine with Al to form AlN, significantly increasing the amount of nitrides in the steel. When AlN exists independently as a non-metallic inclusion in steel, it disrupts the continuity of the steel matrix, especially at higher Al content, resulting in a larger quantity of AlN that aggregates, causing even greater harm. It also forms oxides with poor plasticity. Furthermore, higher N levels tend to accumulate at defects, worsening low-temperature impact toughness. Therefore, in this invention, N is controlled as an impurity element, with the N content controlled to ≤0.0050%.

[0033] In addition to the elements mentioned above, to further improve performance, one or more of W, Sb, RE, V, and Ca can be added to the steel. The specified ranges for each element are: W: 0.01-0.5%, Sb, RE, and V: 0.02-0.12%, Ca: 0.001-0.01%.

[0034] Tungsten: W forms carbides in steel, producing secondary strengthening and solid solution strengthening effects, and suppresses the segregation of impurity atoms and non-metallic inclusions at grain boundaries during overaging, thereby improving fracture toughness.

[0035] Rare earth elements: The addition of RE (rare earth) is beneficial to the improvement of corrosion resistance. In steel, it forms RE compounds, RE / Fe intermetallic compounds and solid solution rare earths, which will hydrolyze in the thin corrosion film and precipitate at the cathodic site with a high pH value, thus playing a role in corrosion inhibition.

[0036] Antimony (Sb) can combine with Cu in steel to form a Cu2Sb film on the surface, thereby improving corrosion resistance.

[0037] Vanadium: It is also a strong carbonitride compound forming element, which can precipitate during phase transformation. In steel, it has the effects of solid solution strengthening and carbonitride precipitation strengthening, and increases tempering stability, thereby improving strength.

[0038] Calcium: Adding Ca to steel can change the shape of sulfides, inhibit the hot brittleness of S, and improve toughness.

[0039] The key point of this invention lies in solving the problem of ultra-high strength steel's poor corrosion resistance and short service life in acidic media. Although ultra-high strength steel has very high hardness, it is like ordinary carbon steel in acidic environments, leading to premature failure of structural components. This invention combines the failure mechanism of steel materials in acidic media environments and, while ensuring high strength and high hardness, effectively improves corrosion resistance through the combination of various corrosion-resistant elements such as Cu, Cr, Mo, and Al. The addition of Cu and Cr increases the matrix potential on the one hand, and on the other hand, Cu combines with sulfur in the steel, improving corrosion resistance in acidic media.

[0040] However, simply adding Cu and Cr does not improve corrosion resistance in acidic environments. Studies have found that adding about 1% Cr to steel increases the self-corrosion potential by approximately 40 mA. Corrosion evaluation results indicate that no significant galvanic corrosion occurs when the potential difference is below 70 mA. Therefore, a 40 mA corrosion potential difference does not significantly change the corrosion current or the corrosion tendency, and has little effect on improving corrosion resistance. Cu is currently an essential element in acid-resistant steels, but approximately 0.1% Sb must also be added to achieve the desired corrosion resistance. This invention, considering environmental and human health factors, selectively adds or minimizes the addition of Sb. Therefore, without any Sb, relying solely on Cr and Cu cannot achieve excellent corrosion resistance in acidic environments.

[0041] The key to the excellent corrosion resistance of the steel grade of this invention in acidic environments lies in the synergistic effect of Cr and Mo. Mo is commonly used in high-strength steels to improve hardenability and tempering stability, or to inhibit pitting corrosion in high-Cr corrosion-resistant steels, thereby improving the steel's corrosion resistance in seawater. However, its content is usually above 0.2%, even as high as 0.5%, which significantly increases costs. This invention has found that in acidic environments, a combination of no more than 0.15% Mo and Cr can significantly improve the corrosion resistance of the steel, but the relationship between its content and the improvement effect is not linear. Analysis suggests that this unique synergistic effect may be related to the fact that Cr and Mo belong to the same group in the periodic table. Both belong to Group 6 subgroup elements and are adjacent, thus possessing similar chemical properties and electronic characteristics, making them easy to combine. The synergistic effect of these two elements simultaneously increases the self-corrosion potential and charge transfer resistance of the steel in acidic media containing large amounts of sulfate and chloride ions, reduces the corrosion current density, and the enrichment of Mo within the rust layer effectively hinders further corrosion of the matrix, thereby significantly improving its corrosion resistance.

[0042] Furthermore, the steel described in this invention also contains 0.015–0.15% Al. Al itself is relatively reactive and readily reacts with oxygen in the air. Under natural conditions, it exhibits a passivation effect, forming a thin Al₂O₃ film on the surface, thus providing corrosion resistance. According to the research of this invention, Cr and Al form intermetallic compounds Fe₂CrAl and Cr₈Al₅ in the steel. Under acidic conditions, these two compounds accumulate on the surface of the steel, improving its corrosion resistance.

[0043] In this invention, Cu and Cr are used to increase the matrix potential. Cu combines with S in the steel, improving corrosion resistance in acidic environments. Simultaneously, Cr combines with Mo and Al in a specific ratio, further promoting corrosion resistance in acidic environments. Therefore, the content of these three elements must meet the requirement of Cr / (Mo / 1.85+1.93Al)≥1.8. Besides Al, the other three alloys also improve strength. Cu, Mo, and Cr all have solid solution strengthening effects, and Cu can also disperse and precipitate in the steel matrix, thus increasing strength. The addition of Mo and Cr also improves the hardenability and tempering resistance of the steel, thereby increasing strength. It is through the combination of these multiple elements that the steel plate achieves a comprehensive performance of high strength and resistance to acidic media corrosion.

[0044] The steel grade designed with the above-mentioned composition not only possesses high strength and hardness but also a high self-corrosion potential, effectively inhibiting corrosion in acidic media and improving corrosion resistance. After heat treatment, it obtains a high-strength martensitic structure with a yield strength ≥1100MPa, tensile strength ≥1300MPa, elongation ≥12%, hardness 450±30HBW, and impact energy ≥60J at -40℃. It exhibits excellent wear resistance, and with the improved corrosion resistance, the steel grade demonstrates good corrosion and wear resistance in acidic media environments, with corrosion resistance more than four times that of ordinary carbon steel and a relative corrosion rate of less than 25%.

[0045] The production method of the 1300MPa grade acid-resistant ultra-high strength steel plate of the present invention includes the following steps:

[0046] 1) Smelting and casting

[0047] Steel is produced and refined in a converter or electric furnace according to the above chemical composition, and then continuously cast into billets.

[0048] 2) Heating

[0049] The billet heating temperature is ≥1230℃, and the holding time is ≥2h, of which the soaking holding time is ≥40min;

[0050] 3) Rolling

[0051] For roughing, the single-pass rolling reduction rate is >15% or the single-pass rolling reduction is >25mm, and the total deformation ratio in the roughing stage is >80%; for finishing, the final pass rolling reduction rate is >16%.

[0052] 4) Cooling

[0053] The rolled steel sheet is cooled to 600-680℃ and then coiled.

[0054] 5) Uncoiling, straightening, and cutting

[0055] 6) Heat treatment

[0056] Quenching, the steel plate is heated to A c3 The steel plate is heated to +(-5~20)℃, and then held at that temperature for a holding time of t=(1.5~2.0)h, where h is the thickness of the steel plate in mm. It is then cooled to room temperature.

[0057] Tempering: The quenched steel plate is heated to 200-240℃. After the core of the steel plate reaches the heating temperature, it is held at that temperature for a holding time of t = (2.0-3.0)h ≥ 10min, where h is the thickness of the steel plate in mm. Then it is cooled to room temperature.

[0058] Preferably, in step 2), the billet is directly hot-charged into the furnace, or the billet is first slowly cooled in a heat preservation pit to below 200°C, then air-cooled, and then heated.

[0059] Preferably, in step 3), the finishing rolling temperature is ≥860℃.

[0060] Preferably, in step 4), the cooling is laminar flow cooling.

[0061] Preferably, in step 6), after quenching, the material is cooled to room temperature at a cooling rate of ≥30℃ / s.

[0062] In the production method of the 1300MPa grade acid-resistant ultra-high strength steel plate described in this invention:

[0063] The billet can be hot-charged into the furnace after casting. That is, after confirming that there are no quality problems on the surface of the billet, it can be directly transported from the casting area to the heating furnace through the roller conveyor for heating and heat preservation, thereby reducing energy consumption. If it cannot be hot-charged, the cast billet must be placed in the heat preservation pit for slow cooling after casting. It can only be removed from the heat preservation pit and air-cooled after the temperature drops below 200℃.

[0064] Before rolling, the billet is heated and held at a certain temperature. Considering that a trace amount of Ti is added to this steel grade, in order to ensure that the carbonitrides of Ti are fully dissolved, the heating temperature is controlled above 1230℃ and the holding time is above 2 hours, of which the soaking and holding time is not less than 40 minutes.

[0065] Rolling is divided into two stages: roughing and finishing. To obtain a fine initial austenite grain size, the billet is rolled with a large reduction in the roughing stage, controlling the reduction per pass to be above 15% or the reduction per pass to be above 25mm, within the allowable conditions of the mill load. To obtain a fine grain size and good plate shape, the total deformation ratio in the roughing stage is controlled to be greater than 80%, and the reduction rate in the final pass of finishing is controlled to be no less than 16%.

[0066] Because this invention employs offline heat treatment after rolling, there are no special requirements for the rolling temperature of the cast billet. However, to reduce the rolling load, the highest possible final rolling and coiling temperatures are used. Figure 1Based on the continuous transformation curve, the α→γ transformation point of the steel grade is about 813℃. Therefore, it is recommended to use a final rolling temperature of 880℃ or higher to ensure rolling in the complete austenitic region, thereby achieving low rolling load and stable rolling load, which is beneficial to obtaining high-quality plate shape in the future. When the steel plate is thicker, the final rolling temperature can be appropriately reduced, but it should not be lower than 860℃.

[0067] In the cooling process, after rolling, the steel coil is cooled to between 600 and 680°C by laminar flow cooling, and then coiled. If the coiling temperature is too high and the cooling rate is too low, the steel coil will have coarse grains, which will also be detrimental to the coiling machine. If the coiling temperature is too low, bainite structure will easily form, which will increase the strength of the steel plate and increase the difficulty of subsequent uncoiling and straightening.

[0068] After the steel coil is cooled to room temperature, it is uncoiled and straightened before being cut into plates. The steel plates are then quenched and tempered to obtain high strength and hardness, ensuring wear resistance.

[0069] During the quenching stage, the quenching heating temperature directly affects the grain size of the subsequent martensite structure, thus affecting the toughness of the steel plate. To ensure sufficient austenitization of the matrix, the quenching heating temperature is generally set at A. c3 The heating temperature should be 30-50℃ above the critical temperature. Excessive heating temperature can coarsen austenite grains, resulting in coarse martensite after quenching and deterioration of toughness. Conversely, insufficient heating temperature leads to incomplete austenitization, preventing the formation of a fully martensitic structure after quenching and negatively impacting toughness. Excessive quenching holding time also results in coarse grains, increased energy consumption, and higher costs. Insufficient holding time leads to incomplete austenitization, resulting in insufficient hardness and strength after quenching. To achieve outstanding low-temperature toughness, this invention employs a critical zone quenching process for the steel plate. The critical zone quenched microstructure contains undissolved acicular ferrite. While this reduces strength, under external force, it reaches the strength limit before martensite, allowing cracks to initiate and propagate within this area, absorbing energy and thus improving toughness. Therefore, it is necessary to control the quenching heating temperature within A... c3 The temperature should be between -5℃ and +20℃, i.e., between 810℃ and 835℃, to achieve better low-temperature toughness. The holding time should be calculated from the core of the steel plate to the start of the heating temperature, and should be 1.5-2 times the thickness of the steel plate (mm) (min). After the steel plate is taken out of the furnace, it should be directly water-quenched to room temperature, requiring a cooling rate ≥30℃ / s.

[0070] In the tempering heat treatment process, the main purpose is to reduce and eliminate quenching stress, and improve toughness and plasticity. Higher tempering temperatures can easily lead to excessive reductions in the strength and hardness of the steel plate, failing to meet design requirements and increasing costs. Therefore, the tempering process parameters for steel plates should be limited. In this invention, the tempering heating temperature is controlled within the range of 200–240°C. The tempering holding time is started from the core of the steel plate reaching the desired temperature, and the tempering holding time t = (2.0–3.0) h, where h is the thickness of the steel plate in mm, but must not be less than 10 min.

[0071] Finally, the heat-treated steel plates undergo finishing treatment (straightening and edge trimming), and are released from the factory after passing the performance test.

[0072] The beneficial effects of this invention are:

[0073] In terms of composition design, this invention supplements the C-Mn base with small amounts of Nb, Ti microalloying elements, and Cu, Cr, Al, Mo, etc. Cu, Mo, and Cr enhance the steel's strength; the synergistic effect of Cu and Cr increases the matrix potential; and the combination of Al and Mo, satisfying the relationship Cr / (Mo / 1.85+1.93Al)≥1.8, improves the self-corrosion potential and charge transfer resistance of the steel in acidic media containing large amounts of sulfate and chloride ions, reduces the corrosion current density, and thus enhances the steel's corrosion resistance. Furthermore, it was found that the aggregation of intermetallic compounds formed by Mo, Cr, and Al on the steel surface can further improve the steel's corrosion resistance. While ensuring high strength and high hardness, this invention also provides excellent corrosion resistance in acidic media. Moreover, the steel plate obtained by this invention exhibits good low-temperature impact toughness and cold bending performance, meeting the requirements of subsequent processing and use.

[0074] Based on the composition design, this invention employs offline heat treatment after rolling and uses sub-temperature quenching in the heat treatment process. This reduces production energy consumption and improves the low-temperature impact toughness of the steel, thereby reducing production difficulty and cost and facilitating the widespread promotion of the steel grade.

[0075] The steel plate obtained by this invention, after heat treatment, acquires a high-strength martensitic structure. The ultra-high-strength steel plate has a yield strength ≥1100MPa, tensile strength ≥1300MPa, elongation ≥12%, hardness 450±30HBW, and impact energy value at -40℃ ≥60J. It exhibits excellent wear resistance, and with improved corrosion resistance, the steel plate demonstrates good corrosion and wear resistance in acidic media containing large amounts of sulfate and chloride ions. Its corrosion resistance is more than four times that of ordinary carbon steel, with a relative corrosion rate of less than 25%. It can be used to manufacture mining equipment, dump truck bodies, sanitation vehicle bodies, chemical equipment, etc., effectively extending the service life of equipment and reducing costs. Attached Figure Description

[0076] Figure 1 This is the CCT curve of the ultra-high strength steel plate described in this invention. Detailed Implementation

[0077] The present invention will be further described below with reference to the embodiments.

[0078] The production process of the ultra-high strength steel plate of the present invention is as follows: smelting, casting → heating → rolling → cooling → uncoiling, straightening, cutting → heat treatment.

[0079] The specific components and process parameters are shown in Tables 1 and 2, and the steel plate properties of each embodiment are shown in Table 3.

[0080] Among them, Comparative Example 1 is "A wear-resistant steel plate with low crack sensitivity index and high strength and its preparation method" disclosed in Chinese Patent Publication No. CN103397272A; Comparative Example 2 is "A high-hardness wear-resistant steel plate for slurry dredging and its production method" disclosed in Chinese Patent Publication No. CN10893001A; Comparative Example 3 is "A hot-rolled steel plate for railway freight cars resistant to atmospheric corrosion and its manufacturing method" disclosed in Chinese Patent Publication No. CN102268613A. Comparative Examples 4 to 7 are currently conventional 450HBW grade wear-resistant steels.

[0081] Corrosion resistance test: The corrosion resistance of the test steel to acidic media was tested in a 10% H2SO4 + 3.5% NaCl solution at a temperature of 23±2℃ for a test period of 24 hours. The corrosion comparison steel was Q345B.

[0082] The steel grade described in this invention has significant differences in composition and properties compared with Comparative Example 1, Comparative Example 2 and Comparative Example 3.

[0083] In terms of composition, the steel grade of this invention achieves both wear resistance and resistance to acidic media corrosion by adding elements such as Cr, Mo, Al, Ti, and Nb to the C-Mn base. In contrast, Patent 1 has low C and Cr content and only adds no more than 0.3% Ni, thus lacking corrosion resistance; Patent 2 has a higher Al content and contains no Si; while Patent 3 contains more corrosion-resistant elements, it lacks strengthening elements, resulting in insufficient strength and hardness to meet the requirements of wear-resistant steel, and also requires the addition of elements such as Mg and Ce, leading to higher costs. The composition design of this invention differs from Comparative Examples 1, 2, and 3.

[0084] Furthermore, the performance of the ultra-high strength steel plate of this invention differs from that of Comparative Examples 1, 2, and 3. The ultra-high strength steel plate of this invention has a yield strength exceeding 1100 MPa and a hardness reaching 450 HBW, thus exhibiting excellent wear resistance, an elongation ≥12%, and a low-temperature impact energy value ≥60 J at -40℃. It also demonstrates excellent corrosion resistance, particularly in acidic corrosive media, with a corrosion rate ≤25% compared to ordinary carbon steel.

[0085] This is something that steels in Comparative Examples 1, 2, and 3 do not possess. The low-temperature impact toughness of steels in Comparative Examples 1, 2, and 3 is not as good as that of this application. Among them, although Comparative Steel 2 has certain resistance to seawater corrosion, it is not resistant to acidic media corrosion; although Comparative Steel 3 has certain resistance to acidic media corrosion, its strength is too low and it does not essentially belong to the category of wear-resistant steel.

[0086] Compared with ordinary carbon steel, conventional 450HBW wear-resistant steel in Comparative Examples 4-7 has virtually no corrosion resistance in acidic media, with a relative corrosion rate exceeding 100%.

[0087] The ultra-high strength steel plate prepared by this invention can be used in mining equipment and machinery, dump truck bodies, sanitation vehicle bodies, chemical equipment, etc., which are subject to acidic media corrosion, to replace the existing 450HBW grade ordinary wear-resistant steel, thereby improving and extending service life and reducing operating costs.

[0088]

[0089]

[0090]

[0091]

[0092]

[0093]

Claims

1. A 1300MPa grade acid-resistant ultra-high strength steel plate, the chemical composition by weight percentage being: C: 0.17~0.22%, Si: 0.10~0.30%, Mn: 0.80~1.20%, P≤0.018%, S≤0.010%, Al: 0.015~0.15%, Cu: 0.15~0.35%, Cr: 0.50~1.20%, Mo: 0.02~0.15%, B: 0.0010~0.0030%, N≤0.005%, containing one or both of Nb: 0.01~0.03% and Ti: 0.01~0.03%, with the balance being Fe and other unavoidable impurities; and the above elements must simultaneously satisfy the following relationship: Cr / (Mo / 1.85+1.93Al)≥1.8; The ultra-high strength steel plate has a yield strength ≥1100MPa, tensile strength ≥1300MPa, elongation ≥12%, hardness 450±30HBW, impact energy value at -40℃ ≥60J, corrosion resistance is more than 4 times that of ordinary carbon steel, and relative corrosion rate is less than 25%.

2. The 1300MPa grade acid-resistant ultra-high strength steel plate as described in claim 1, characterized in that, The balance consists of Fe and other unavoidable impurities.

3. The 1300MPa grade acid-resistant ultra-high strength steel plate as described in claim 1 or 2, characterized in that, It also contains one or more of the following: W: 0.01~0.5%, Sb: 0.02~0.12%, RE: 0.02~0.12%, V: 0.02~0.12%, and Ca: 0.001~0.010%.

4. The 1300MPa grade acid-resistant ultra-high strength steel plate as described in claim 1 or 2, characterized in that, The microstructure of the ultra-high strength steel plate is martensitic.

5. The 1300MPa grade acid-resistant ultra-high strength steel plate as described in claim 3, characterized in that, The microstructure of the ultra-high strength steel plate is martensitic.

6. The method for producing 1300MPa grade acid-resistant ultra-high strength steel plate according to any one of claims 1 to 5, characterized in that, Includes the following steps: 1) Smelting and casting The chemical composition described in claim 1, 2 or 3 is used for steelmaking and refining in a converter or electric furnace, followed by continuous casting into billets. 2) Heating The billet heating temperature is ≥1230℃, and the holding time is ≥2h, of which the soaking holding time is ≥40min; 3) Rolling For roughing, the single-pass rolling reduction rate is >15% or the single-pass rolling reduction is >25mm, and the total deformation ratio in the roughing stage is >80%; for finishing, the final pass rolling reduction rate is >16%. 4) Cooling After final rolling, the steel plate is cooled to 600~680℃, and then coiled or air-cooled to room temperature; 5) Uncoiling, straightening, and cutting 6) Heat treatment Quenching: The steel plate is heated to Ac3 + (-5~20)℃. After the core of the steel plate reaches the heating temperature, it is held at that temperature for a holding time of t = (1.5~2.0) h, in minutes; where h is the thickness of the steel plate, in mm; then cooled to room temperature. Tempering: The quenched steel plate is heated to 200~240℃. After the core of the steel plate reaches the heating temperature, it is held at that temperature for a holding time of t=(2.0~3.0)h≥10min, where h is the thickness of the steel plate in mm. Then it is cooled to room temperature.

7. The production method of 1300MPa grade acid-resistant ultra-high strength steel plate as described in claim 6, characterized in that, In step 2), the billet is directly hot-charged into the furnace, or the billet is first slowly cooled in a heat preservation pit to below 200°C, then air-cooled and then heated.

8. The method for producing 1300MPa grade acid-resistant ultra-high strength steel plate as described in claim 6, characterized in that, In step 3), the finishing rolling temperature is ≥860℃.

9. The method for producing 1300MPa grade acid-resistant ultra-high strength steel plate as described in claim 6, characterized in that, In step 4), the cooling is performed using laminar flow cooling.

10. The method for producing 1300MPa grade acid-resistant ultra-high strength steel plate as described in claim 6, characterized in that, In step 6), after quenching, the material is cooled to room temperature at a cooling rate of ≥30℃ / s.

Citation Information

Patent Citations

  • A hot-rolled steel plate resistant to atmospheric corrosion for railway freight cars and its manufacturing method

    CN102268613A

  • Low-alloy high-strength-toughness wear-resistant steel plate

    CN103103448A

  • Abrasion-resistant steel plate with low crack sensitive index and high strength and preparation method thereof

    CN103397272A

  • High-hardness wear-resistant corrosion-resistant steel plate for slurry dredging and production method thereof

    CN108930001A

  • High workability and good weldability sulfuric acid dew point corrosion resistant steel sheet

    JP2001164335A